Taxifolin, an Inhibitor of Sortase A, Interferes With the Adhesion of Methicillin-Resistant Staphylococcal aureus - Wang, Li; Wang, Guangming; Qu, Han; Wang, Kai; Jing, Shisong; Guan, Shuhan; Su, Liyan; Li, Qianxue; Wang, Dacheng (Frontiers in Microbiology, 2021)
The evolution and spread of methicillin-resistant Staphylococcus aureus (MRSA) poses a significant hidden risk to human public health. The majority of antibiotics used clinically have become mostly ineffective, and so the development of novel anti-infection strategies is urgently required. Since Staphylococcus aureus (S. aureus) cysteine transpeptidase sortase A (SrtA) mediates the surface-anchoring of proteins to its surface, compounds that inhibit SrtA are considered potential antivirulence treatments. Herein, we report on the efficacy of the potent SrtA inhibitor taxifolin (Tax), a flavonoid compound isolated from Chinese herbs. It was able to reversibly block the activity of SrtA with an IC50 of 24.53 ± 0.42 μM. Tax did not display toxicity toward mammalian cells or S. aureus at a concentration of 200 μM. In addition, Tax attenuated the virulence-related phenotype of SrtA in vitro by decreasing the adherence of S. aureus, reducing the formation of a biofilm, and anchoring of S. aureus protein A on its cell wall. The mechanism of the SrtA-Tax interaction was determined using a localized surface plasmon resonance assay. Subsequent mechanistic studies confirmed that Asp-170 and Gln-172 were the principal sites on SrtA with which it binds to Tax. Importantly, in vivo experiments demonstrated that Tax protects mice against pneumonia induced by lethal doses of MRSA, significantly improving their survival rate and reducing the number of viable S. aureus in the lung tissue. The present study indicates that Tax is a useful pioneer compound for the development of novel agents against S. aureus infections.